Topics in the Routine Assessment of Newborn Puppy Viability - Vassalo, Flavia Gardilin [UNESP]; Barbieri Simoes, Carla Regina [UNESP]; Sudano, Mateus Jose; Prestes, Nereu Carlos [UNESP]; Lopes, Maria Denise [UNESP]; Chiacchio, Simone Biagio [UNESP]; Comes Lourenco, Maria Lucia [UNESP] (Elsevier B.V., 2015)
Neonatal veterinarians still observe higher mortality rates among their patients than those observed among humans. Establishment of a neonatal assessment protocol is fundamental to the identification of the medical status of the neonate and the need for medical intervention. The neonatal Apgar score evaluation, which is commonly used in clinical practice, should be complemented by other methods of analysis. This study proposes, in addition to an Apgar score analysis, the evaluation of laboratory parameters and weight. We believe that knowledge of these reference values is essential for diagnosing at-risk neonates and for establishing suitable treatments.
Keywords: Neonate; Small animals; Canine; Apgar score; Blood gas; Neonatal reflexes